1980
DOI: 10.1002/jsfa.2740311212
|View full text |Cite
|
Sign up to set email alerts
|

The production of milk rich in protein and low in fat, the fat having a high polyunsaturated fatty acid content

Abstract: In two experiments, dairy heifers were offered a basal diet of ground dried grass cubes and flaked maize. In Experiment 1, the diet contained equal amounts of these components whereas, in Experiment 2, the proportions were varied from all-grass to equal amounts of grass and flaked maize. Before and after the main part of each experiment, the animals were offered a diet containing hay, molassed sugar beet pulp and barleybased concentrates. Compared to this diet, the grass cubes-flaked maize diet reduced the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Because of the biohydrogenation occurring in the rumen, milk and other dairy products are a major contributor to dietary saturated fatty acid, which has led to a negative consumer perception and a public health concern related to excessive intake of saturated fats [ 40 ]. There have been numerous researches carried out during the last three decades to improve the FA profiles of the products of ruminants [ 41 44 ], and there was not enough evidence of direct relationship between PUFA and health, however, further studies indicated PUFA content of the foods did affect some indicators of health status [ 45 47 ]. Compared with the control group, milk PUFA of cows are significantly higher (p<0.05), and saturated fats (C4:0, C17:0) are significantly lower (p<0.05) in group M and group H, which might be caused by the reduced biohydrogenation of unsaturated fatty acids in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the biohydrogenation occurring in the rumen, milk and other dairy products are a major contributor to dietary saturated fatty acid, which has led to a negative consumer perception and a public health concern related to excessive intake of saturated fats [ 40 ]. There have been numerous researches carried out during the last three decades to improve the FA profiles of the products of ruminants [ 41 44 ], and there was not enough evidence of direct relationship between PUFA and health, however, further studies indicated PUFA content of the foods did affect some indicators of health status [ 45 47 ]. Compared with the control group, milk PUFA of cows are significantly higher (p<0.05), and saturated fats (C4:0, C17:0) are significantly lower (p<0.05) in group M and group H, which might be caused by the reduced biohydrogenation of unsaturated fatty acids in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Fats that escape biohydrogenation in tf,e rumen can increase the supply of unsaturated fatty acids to milk (Clapperton et al 1980). If rhe long-chain fatty acids are relatively saturated, the C1s.s fatty acid can be desaturated to C1s 1 (Banks et al 1976).…”
mentioning
confidence: 99%
“…These values are similar to those quoted by other authors. Garrett et al 7 found that the apparent digestibility of the ether extract of protected vegetable oil was 85-88 % when added at 15 or 30 % of the basal ration. They also quote other values ranging from 70% for a safflower oil/protected casein complex (Hogan et a[.…”
Section: Apparent Digestibilitymentioning
confidence: 99%